SISTEM PEMANTAUAN KONSUMSI AIR BERSIH BERBASIS IoT MENGGUNAKAN SENSOR ALIRAN DAN KUALITAS AIR DENGAN ARDUINO DAN BLYNK - Anjani, Raisha; Fitriani, Endah (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2025)
Clean water is an important aspect of the human body, around 60-70% of the total composition of other elements. The availability of drinking water of adequate quality is a primary human need to maintain health and well-being, however, there is a lot of drinking water that is not suitable for consumption according to its suitability. The supply of clean water is also starting to run low while the use of clean water is increasing. The aim of designing this monitoring system is to produce a tool that can monitor water quality. This system was created using other devices including Arduino Mega 2560, Esp32 microcontroller, turbidity sensor, TDS meter sensor, flow meter sensor, and float switch sensor and using the Internet. Things with Blynk as the notification output and LCD as the display. This system is expected to help users find out the quality of the water they use.Keywords: Clean water, ESP32, Turbidity, TDS Meter, Flow Meter